1984
DOI: 10.2118/12020-pa
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Hydraulic Parameters for the Canirnenellis Granite Hot Dry Rock Geothermal Energy Research Reservoir

Abstract: Summary A research hot dry rock (HDR) geothermal energy reservoir is currently under development in the Carnmenellis granite in Cornwall, U.K., at a depth of about 6,600 ft [2000 m]. This paper details the performance, analysis, and interpretation of hydraulic tests using low to medium pressures and flow rates. These tests allowed an evaluation pressures and flow rates. These tests allowed an evaluation of the in-situ hydraulic parameters relevant to initial water storage and long-term leakag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The decrease in permeability corresponded to a decrease in the intensity of open and flowing fractures (Follin et al 2014). Other sparsely fractured granites have similarly low permeability, including the Carnmenellis batholith, for which Pine and Ledingham (1984) calculated a permeability on the order of 10 -17 m 2 between 1,500 and 2,000 m depth, and the Lac du Bonnet batholith, in which Stevenson et al (1996) found permeabilities between 3x10 -17 m 2 and 2.5x10 -22 m 2 in domains of sparsely fractured rock. Not all granite bodies are sparsely fractured; fracture intensity and style can be related to emplacement history and rate of cooling with small plutons experiencing greater amounts of brittle deformation than large (Stone et al 1989 instead mean values throughout the 9 km borehole are 7x10 -20 m 2 with a log standard deviation of 1.2 (Huenges et al 1997).…”
Section: Deep Borehole Disposal Safety Analysis 78mentioning
confidence: 99%
“…The decrease in permeability corresponded to a decrease in the intensity of open and flowing fractures (Follin et al 2014). Other sparsely fractured granites have similarly low permeability, including the Carnmenellis batholith, for which Pine and Ledingham (1984) calculated a permeability on the order of 10 -17 m 2 between 1,500 and 2,000 m depth, and the Lac du Bonnet batholith, in which Stevenson et al (1996) found permeabilities between 3x10 -17 m 2 and 2.5x10 -22 m 2 in domains of sparsely fractured rock. Not all granite bodies are sparsely fractured; fracture intensity and style can be related to emplacement history and rate of cooling with small plutons experiencing greater amounts of brittle deformation than large (Stone et al 1989 instead mean values throughout the 9 km borehole are 7x10 -20 m 2 with a log standard deviation of 1.2 (Huenges et al 1997).…”
Section: Deep Borehole Disposal Safety Analysis 78mentioning
confidence: 99%